Alternative Splicing of Disabled-1 Controls Multipolar-to-Bipolar Transition of Migrating Neurons in the Neocortex. (22nd August 2017) - Zhang, Bin; Wang, Weiwei; Zhang, Zhenjie; Hu, Yaling; Meng, Fan; Wang, Fan; Lou, Huifang; Zhu, Liya; Godbout, Roseline; Duan, Shumin; Gao, Zhihua
Abstract: Multipolar-to-bipolar transition (MBT) is crucial for the neuronal migration and positioning in the neocortex. Reelin-Disabled-1 (Dab1) signaling plays a pivotal role in neuronal migration, yet how Dab1 coordinatively regulates downstream molecules to affect MBT remains unclear. We have previously found that alternative splicing produces multiple Dab1 isoforms with different tyrosine motifs and differential ability to recruit downstream effectors. Here, we report that splicing of Dab1 exons 7 and 8 and 9bc dynamically regulates the inclusion and activities of Dab1 tyrosine motifs in the neocortex. By in utero electroporation, we show that expression of Dab1 isoforms missing exons 7 and 8 or retaining exons 9bc in WT neurons resulted in neuronal migration defects with attenuated Dab1 tyrosine phosphorylation, disrupted leading process extension, and disorientated multipolar neurons in the multipolar accumulation zone. Introducing the canonical Dab1 form, but not those missing exons 7 and 8 or retaining exons 9bc, into Dab1-deficient neurons promoted MBT and rescued neuronal migration defects, suggesting that alternative splicing of Dab1 modulates the tyrosine motif switch and mediates MBT of cortical neurons. Our study reveals a critical mechanism by which Dab1 alternative splicing coordinately controls MBT and neuronal migration in a spatiotemporal manner.